Analisis Konsep Poligami dalam Al-Qur’an (Studi Tafsir AL-Misbah oleh M. Quraish Shihab) - Siti Asiyah; Rakhmat Rakhmat; Habib Ismail; Ari Rohmawati (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2018)
The polemic about polygamy is increasingly prominent and attracts attention when the practice of polygamy is openly carried out by public figures ranging from entrepreneurs, politicians, scholars, to comedians. Even the conversation about polygamy never seems to stop. Recently, conversations have turned into interesting debates, especially since the post-New Order era. Polygamy was "regulated" by the Government through the Republic of Indonesia Government Regulation number 9 of 1975 concerning the implementation of Law No. 1 of 1974 concerning Marriage. Many Muslim nations currently consider unconstitutional polygamy to justify changes in legislation based on the Qur'anic perspective on marriage, as well as the perspective of modern Islamic marriage. In this regard, the writer tries to analyze the concept of polygamy in interpretation. Quraish Shihab offers the concept of polygamy in his interpretation of Al-Misbah Surat An-Nisa verses 3 and 129. This research is a qualitative research using content analysis method.